Learning Methods Based on Deaf Children's Learning Styles - Fitriyani, Fachrurozi, Novita Cahya, Rahma Fazriyah, (ALACRITY : Journal of Education, 2023)
The problems taken from this research are how learning methods based on learning styles of deaf children at Sekolah Luar Biasa Wijayakusumah Bekasi, to what extent are learning style methods used by deaf students and what difficulties arise when deaf students have different learning styles. The purpose of this study is to describe learning methods that can develop the learning styles of deaf children. The method used in this article is a qualitative method. From the results of the learning process obtained by deaf students at school, students are able to achieve quite good academic learning outcomes. This makes deaf students able to equalize their abilities with other normal children.